Приобретение права собственности на самовольную постройку - Dobrynina, Olga (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The study aims at an evaluation of the acquisition of the ownership of the unauthorised construction. The author present this form of the acquisition of the right to property in the civil code of the Russian Federation emphasising the necessity of fulfilling law norms.
The acquisition of the ownership of the unauthorised construction
Keywords: unauthorised construction; acquisition of the ownership; civil law